Build, buy, or partner? A systematic literature review on the choice between alternative modes of growth - Philipp Ego (Management Review Quarterly, 2022)
When pursuing growth opportunities, organizations can, most fundamentally, choose between three different modes: internal development, mergers and acquisitions, and partnerships. Strategic management research investigates the decision of whether to "build, buy, or partner" and its determining factors from various theoretical perspectives, which led to the emergence of related, but largely independent, research streams. As such, this review consolidates the scattered literature landscape and provides a comprehensive understanding of the antecedents associated with the choice of corporate growth modes. To do so, an integrative research framework is proposed that encompasses internal, external, and decision-related factors. Based on this framework, the review provides a synthesized overview and critical assessment of 74 past empirical contributions and develops a detailed roadmap to guide future research.
Keywords: M10; 650; Growth; Growth strategy; Corporate growth; Strategic decision; Acquisition; Mode choice